Peningkatan Pengetahuan dan Pemberdayaan Masyarakat Desa Wisata Cimande melalui Usaha Homestay Jawara - Soeswoyo, Dinamayasari; Skarwanti, Julia Ratnawulan; Ishak, Riani P. (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: The aim of this program is to increase the knowledge and empowerment of the Cimande Village community and also the Tourism Awareness Group (POKDARWIS) by utilizing their residences in the Jawara homestay business so that it can provide additional income and improve welfare. Methodology: This program was carried out in three stages, namely the preparation stage which is carried out through observation, FGD and internal discussions; the second stage is implementation with coaching and workshops; and the third stage is evaluation through tests, monitoring and evaluation. Result: The results of the pre-test and post-test evaluation showed that the level of knowledge and understanding of the participants increased from initially not understanding to understanding. The participant's skill level increased in making the bed and cleaning the bathroom, and the participants were able to create social media accounts and content about the homestay. Conclusion: The community empowerment program through the homestay business will run optimally if it is well prepared based on the needs, commitment, and participation of the village community, and implemented by providing knowledge, skills, and equipment assistance according to standards, as well as providing assistance so that the community can become independent. Limitation: This article has limitations in terms of the number of community participants who are interested in homestay business. Contribution: This program contributes as a reference for other scholars in efforts to develop homestays in tourist villages. This program also contributes to the Cimande Village Community in managing, developing homestays according to standards, and marketing them.